Effects of novel triple-stage antimalarial ionic liquids on lipid membrane models. Issue 17 (1st September 2017) - Ferraz, Ricardo; Pinheiro, Marina; Gomes, Ana; Teixeira, Cátia; Prudêncio, Cristina; Reis, Salette; Gomes, Paula
Graphical abstract: Abstract: Primaquine-based ionic liquids, obtained by acid-base reaction between parent primaquine and cinnamic acids, were recently found as triple-stage antimalarial hits. These ionic compounds displayed significant activity against both liver- and blood-stage Plasmodium parasites, as well as against stage V P. falciparum parasites. Remarkably, blood-stage activity of the ionic liquids against both chloroquine-sensitive (3D7) and resistant (Dd2) P. falciparum strains was clearly superior to those of the respective covalent (amide) analogues and of parent primaquine. Having hypothesized that such behaviour might be ascribed to an enhanced ability of the ionic compounds to permeate into Plasmodium -infected erythrocytes, we have carried out a differential scanning calorimetry-based study of the interactions between the ionic liquids and membrane models. Results provide evidence, at the molecular level, that the primaquine-derived ionic liquids may contribute to an increased permeation of the parent drug into malaria-infected erythrocytes, which has relevant implications towards novel antimalarial approaches based on ionic liquids.